2006
DOI: 10.1631/jzus.2006.b0118
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracic surgery—The past, present status and the future

Abstract: Video-assisted thoracic surgery (VATS) has developed very rapidly in these two decades, and has replaced conventional open thoracotomy as a standard procedure for some simple thoracic operations as well as an option or a complementary procedure for some other more complex operations. In this paper we will review its development history, the present status and the future perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 115 publications
(114 reference statements)
0
50
0
3
Order By: Relevance
“…My series has some experiences of VATS procedures in the supine position, for SP as well as other types of diseases, such as empyema, emphysema, interstitial lung diseases or pulmonary nodular lesions (Luh and Liu, 2006;Luh et al, 2004;. Consideration of the supine position for VATS usually depends on the condition of patients and the location of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…My series has some experiences of VATS procedures in the supine position, for SP as well as other types of diseases, such as empyema, emphysema, interstitial lung diseases or pulmonary nodular lesions (Luh and Liu, 2006;Luh et al, 2004;. Consideration of the supine position for VATS usually depends on the condition of patients and the location of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Resection is also valuable to help determine further treatment strategies and decrease the duration and dose of anti-tuberculosis treatment. In many cases, bronchoscopic or needle biopsy are not practically possible, and VATS is therefore a good minimally invasive option (20). Authors from Taiwan (21) reported 53 cases of tuberculoma that underwent VATS.…”
Section: Surgical Treatment Of Pulmonary Tuberculomamentioning
confidence: 99%
“…Later, as VATS became more popular within thoracic surgery, further development brought two-port configurations, robotic assisted surgery and needlescopic approaches. VATS was also introduced into use for increasingly complex operations including mediastinal masses, large resections and cases with chest wall involvement (12). The old rules regarding absolute contraindications for VATS and the standard indications for open thoracotomy were broken with excellent results.…”
Section: Evolution To Video-assisted Thoracoscopic Surgerymentioning
confidence: 99%